Aplikasi Metode SRI (System Rice of Intensification) dan Sistem Tanam Jajar Legowo Terhadap Iklim Mikro yang Mempengaruhi Produktivitas Padi Beras Merah - Paul Ludgerius Rusman Pita; I Made Nada; Sumiyati Sumiyati (Jurnal BETA (Biosistem dan Teknik Pertanian), 2016)
This research was carried out to know the result of the application method system of rice intensification (SRI) which was combined with rice planting system legowo in raw toward micro climate which influence the productivity of red rice. These research was consist of 6 treatments, they were : K0 (the treatment which appropriated to local farmers custom), K1 (SRI method), K2 (SRI method combined with legowo 4:1 inserting), K3 (SRI method combined with legowo 4:1 without inserting), K4 (SRI method combined with legowo 6:1 inserting), and K5 (SRI method with legowo 6:1 without inserting). This treatment study was repeated 3 times. Parameters observed were : relativity of humidity, temperature, intensity of sun shine, the length of stalk, the weight of rice in a clump, percentage pure rice, the weight of 1000 pure rice, the number of young plants in a clump, the number of young plants and each productivity. The outcome of this research shown that the application of SRI method combined with legowo 4:1 without inserting got more intensity of sun shine and the highest temperature, while the application of K0 had the highest relativity weakness. Application SRI method with legowo 6:1 without inserting produced the highest product in average per width of area, there were 7,48 ton/ ha, comparing with other applications.